2014
DOI: 10.3389/fnins.2014.00339
|View full text |Cite
|
Sign up to set email alerts
|

Cortical connective field estimates from resting state fMRI activity

Abstract: One way to study connectivity in visual cortical areas is by examining spontaneous neural activity. In the absence of visual input, such activity remains shaped by the underlying neural architecture and, presumably, may still reflect visuotopic organization. Here, we applied population connective field (CF) modeling to estimate the spatial profile of functional connectivity in the early visual cortex during resting state functional magnetic resonance imaging (RS-fMRI). This model-based analysis estimates the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
53
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 55 publications
24
53
3
1
Order By: Relevance
“…This deviation of V3 from the neuro-typical condition was further supported by the comparison of the difference of V1-sampling-extent observed for V2 and V3 (Figure 4 B). While it increased from V2 to V3 in controls (t (3) = 3.24, p = 0.04) as reported previously (Gravel et al, 2014;Haak et al, 2013), no increase was evident for albinism (t (5) =1.1, p =0.32). Taken together, these findings indicate a largely unaltered V1-V2 connectivity in albinism, but suggest an alteration of the functional connectivity for V3.…”
Section: Cf-properties In Albinismsupporting
confidence: 83%
“…This deviation of V3 from the neuro-typical condition was further supported by the comparison of the difference of V1-sampling-extent observed for V2 and V3 (Figure 4 B). While it increased from V2 to V3 in controls (t (3) = 3.24, p = 0.04) as reported previously (Gravel et al, 2014;Haak et al, 2013), no increase was evident for albinism (t (5) =1.1, p =0.32). Taken together, these findings indicate a largely unaltered V1-V2 connectivity in albinism, but suggest an alteration of the functional connectivity for V3.…”
Section: Cf-properties In Albinismsupporting
confidence: 83%
“…Using a 3-D Gaussian modeling approach with whole-brain resting-state fMRI data, we found that closely connected brain regions exhibit a relatively strong linear topology of their functional connectivity. This linear organization of region to region functional connectivity was highly reliable in early visual regions, following a topographic order along the anterior-posterior axis for eccentricity representation, as predicted by the literature Gravel et al, 2014;Haak et al, 2013).…”
Section: Discussionsupporting
confidence: 68%
“…The connective field mapping technique fits 2 dimensional surface based population receptive fields (pRFs) using cortical signal from one region as the input to another region (Haak et al, 2013). This method has been used to model early visual areas, showing maintenance of retinotpic organization across them (Gravel et al, 2014;Haak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With a color arrow, the functional parcellation obtained in this study is shown as the underlay, while an existing parcellation is shown as the overlay. ;de Zwart et al, 2013;Gravel et al, 2014;Heinzle et al, 2011;Raemaekers et al, 2014;Striem-Amit et al, 2015;Wilf et al, 2017;Yeo et al, 2011). In the whole-brain scale, ICA and seed-based correlation analyses have been shown to reveal similar network patterns (Van Dijk et al, 2010).…”
Section: Ica For Fine-scale Functional Connectivitymentioning
confidence: 99%
“…Since much of the visual cortex has visual-field maps-topographic representations of the polar angle and eccentricity (Wandell et al, 2007), it is reasonable to initially speculate that resting state activity is intrinsically organized by retinotopy. Support for this hypothesis comes in part from the finding that in early visual areas (e.g., V1-V3), correlations in spontaneous activity are generally higher between locations with similar eccentricity representations (Arcaro et al, 2015;Dawson et al, 2016;Genc et al, 2016;Gravel et al, 2014;Heinzle et al, 2011;Jo et al, 2012;Lewis et al, 2016;Striem-Amit et al, 2015;Yeo et al, 2011). However, such eccentricity-dependent functional connectivity has rarely been reported beyond early visual areas (Baldassano et al, 2013;Striem-Amit et al, 2015); it may be relatively weak (Wilf et al, 2017) or observable only after regressing out large-scale activity (Raemaekers et al, 2014), and may also be confounded by the decay of local connectivity over cortical distance (Butt et al, 2013;Dawson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%